Applying dynamic systems theory and complexity theory methods in psychotherapy research: A systematic literature review - Klocek, Adam; Premus, Jan; Řiháček, Tomáš (Psychotherapy research, 2024)
OBJECTIVE: Dynamic systems theory and complexity theory (DST/CT) is a framework explaining how complex systems change and adapt over time. In psychotherapy, DST/CT can be used to understand how a person's mental and emotional state changes during therapy incorporating higher levels of complexity. This study aimed to systematically review the variability of DST/CT methods applied in psychotherapy research. METHODS: A primary studies search was conducted in the EBSCO and Web of Knowledge databases, extracting information about the analyzed DST/CT phenomena, employed mathematical methods to investigate these phenomena, descriptions of specified dynamic models, psychotherapy phenomena, and other information regarding studies with empirical data (e.g., measurement granularity). RESULTS: After screening 38,216 abstracts and 4,194 full texts, N = 41 studies published from 1990 to 2021 were identified. The employed methods typically included measures of dynamic complexity or chaoticity. Computational and simulation studies most often employed first-order ordinary differential equations and typically focused on describing the time evolution of client-therapist dyadic influences. Eligible studies with empirical data were usually based on case studies and focused on data with high time intensity of within-session dynamics. CONCLUSION: This review provides a descriptive synthesis of the current state of the proliferation of DST/CT methods in the psychotherapy research field.
Keywords: Adaptation, Psychological; nonlinearity; Humans; systematic review; nelineární dynamika; Systems Theory; Psychotherapy; psychotherapy; Data Visualization; Psychology; differential equations; lidé; vizualizace dat; psychoterapie; chaos theory; teoretické modely; adaptace psychologická; výzkumný projekt; Research Design; Models, Theoretical; Nonlinear Dynamics; systémová teorie; psychologie; complex systems